Nephritis : being part II of several clinical treatises on the pathology and therapy of disorders of metabolism and nutrition - Noorden, Carl von, 1858-1944 (John Wright & Co., 1903)
Nephritis, Part II of Several Clinical Treatises on the Pathology and Therapy of Disorders of Metabolism and Nutrition discusses the most important fundamental principles of the treatment of renal diseases. This book focuses on two chief forms of renal disease- acute nephritis and contracted kidney. The parenchymatous or sub-chronic form of nephritis is only briefly mentioned. Other topics discussed include the customary therapy of kidney diseases; principle of saving the kidneys in renal diseases; and facts of metabolism as a basis for the dietary regulations to be adopted in the protective t.